Amoxapine Demonstrates Incomplete Inhibition of β-Glucuronidase Activity from Human Gut Microbiota. (January 2018) - Yang, Wei; Wei, Bin; Yan, Ru
Amoxapine has been demonstrated to be a potent inhibitor of Escherichia coli β-glucuronidase. This study aims to explore the factors causing unsatisfactory efficacy of amoxapine in alleviating CPT-11–induced gastrointestinal toxicity in mice and to predict the outcomes in humans. Amoxapine (100 µM) exhibited poor and varied inhibition on β-glucuronidase activity in gut microbiota from 10 healthy individuals and their pool (pool, 11.9%; individuals, 3.6%−54.4%) with IC50 >100 µM and potent inhibition toward E. coli β-glucuronidase (IC50 = 0.34 µM). p -Nitrophenol formation from p -nitrophenyl-β-D-glucuronide by pooled and individual gut microbiota fitted classical Michaelis-Menten kinetics, showing similar affinity (Km = 113–189 µM) but varied catalytic capability (Vmax = 53–556 nmol/h/mg). Interestingly, amoxapine showed distinct inhibitory effects (8.7%–100%) toward β-glucuronidases of 13 bacterial isolates (including four Enterococcus, three Streptococcus, two Escherichia, and two Staphylococcus strains; gus genes belonging to OTU1, 2 or 21) regardless of their genetic similarity or bacterial origin. In addition, amoxapine inhibited the growth of pooled and individual gut microbiota at a high concentration (6.3%–30.8%, 200 µM). Taken together, these findings partly explain the unsatisfactory efficacy of amoxapine in alleviating CPT-11–induced toxicity and predict a poor outcome of β-glucuronidase inhibition in humans, highlighting the necessity of using a human gut microbiota community for drug screening.